Political economy, race, and the image of nature in the United States, 1825-1878 - Neely, Evan Robert, 1976- (New York, NY : Routledge, 2024)
"Political Economy, Race, and the Image of Nature in the United States, 1825-1878 is an interdisciplinary work analyzing the historical origins of a dominant concept of Nature in the culture of the United States during the period of its expansion across the continent. Chapters analyze the ways in which "Nature" became a discursive site where theories of race and belonging, adaptation and environment, and the uses of literary and pictorial representation were being renegotiated, forming the basis for an ideal of the human and the nonhuman world that is still with us. Through an interdisciplinary approach involving the fields of visual culture, political economy, histories of racial identity, and ecocritical studies, the book examines the work of seminal figures in a variety of literary and artistic disciplines and puts the visual culture of the United States at the center of intellectual trends that have enormous implications for contemporary cultural practice. The book will be of interest to scholars working in art history, visual culture, American studies, environmental studies/ecocriticism, critical race theory, and semiotics"--
William Cullen Bryant and the semiology of landscape representation -- Cartography, composition, and the place of the painter -- Exploration, environment, and economy -- Racial geography : North of Robert Seldon Duncanson's canvas -- The picturesque garden and the unhandselled globe : Walden and the economy of nature -- Conclusion. A coda on Peirce and the image of nature.
Keywords: Nature (Aesthetics); Philosophy of nature -- United States; Arts, American -- 19th century -- Themes, motives; United States -- Intellectual life -- 1783-1865.; United States -- Intellectual life -- 1865-1918.; ART / History / General; NATURE / Environmental Conservation & Protection